2020
DOI: 10.1002/jmr.2877
|View full text |Cite
|
Sign up to set email alerts
|

Binding of direct oral anticoagulants to the FA1 site of human serum albumin

Abstract: The anticoagulant therapy is widely used to prevent and treat thromboembolic events. Until the last decade, vitamin K antagonists were the only available oral anticoagulants; recently, direct oral anticoagulants (DOACs) have been developed. Since 55% to 95% of DOACs are bound to plasma proteins, the in silico docking and ligand‐binding properties of drugs apixaban, betrixaban, dabigatran, edoxaban, and rivaroxaban and of the prodrug dabigatran etexilate to human serum albumin (HSA), the most abundant plasma pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 54 publications
(99 reference statements)
0
9
0
1
Order By: Relevance
“…Computational studies, using molecular docking approach, have been shown to play an important role to decipher the molecular recognition mechanisms and previewing of binding affinity of drugs and other bioactive compounds on plasma proteins. Recent docking studies for drug-protein interactions analysis encompass, for example, oral anticoagulants [169], the anticancer drug gemcitabine [170], the antihypertensive drug telmisartan [171], among others. Regarding other bioactive compounds, some recent examples include the dihydroxy-phenyl-thiazol-hydrazinium chloride (antioxidant and antiradical activities) [172], hydrazone ligand derived Cu(II) and VO(IV) complexes (antibacterial and antifungal activities) [173], uranyl complexes of alkyl substituted isothiosemicarbazone (anticancer features) [174], 7-amino coumarin derivative (analgesic, anticancer, and anticoagulant activities) [175], among others.…”
Section: In Silico Methodsmentioning
confidence: 99%
“…Computational studies, using molecular docking approach, have been shown to play an important role to decipher the molecular recognition mechanisms and previewing of binding affinity of drugs and other bioactive compounds on plasma proteins. Recent docking studies for drug-protein interactions analysis encompass, for example, oral anticoagulants [169], the anticancer drug gemcitabine [170], the antihypertensive drug telmisartan [171], among others. Regarding other bioactive compounds, some recent examples include the dihydroxy-phenyl-thiazol-hydrazinium chloride (antioxidant and antiradical activities) [172], hydrazone ligand derived Cu(II) and VO(IV) complexes (antibacterial and antifungal activities) [173], uranyl complexes of alkyl substituted isothiosemicarbazone (anticancer features) [174], 7-amino coumarin derivative (analgesic, anticancer, and anticoagulant activities) [175], among others.…”
Section: In Silico Methodsmentioning
confidence: 99%
“…In humans, DOACs are bound to human plasma proteins, primarily to serum albumin, the most abundant human plasma protein. The molar fractions of apixaban, edoxaban, and rivaroxaban bound to human plasma proteins are >87%, ~35%, 55%, and 95%, respectively [29]. LMWHs, in contrast, have low human plasma protein binding [30].…”
Section: Pharmacokinetic Ddis and Drug Transporter Ddismentioning
confidence: 99%
“…In the presence of myristate, several drugs co-bind to the FA7 site. This suggests that myristate causes a conformational change(s) of the binding site resulting in the formation of three non-overlapping secondary sites able to recognize anesthetics, anticoagulants, antineoplastics, antiretrovirals, and non-steroidal anti-inflammatory drugs (NSAIDs) [ 13 , 41 , 73 ] ( Table S1 ).…”
Section: Human Serum Albuminmentioning
confidence: 99%
“…Human serum albumin (HSA) is the most abundant protein in plasma, representing the main determinant of the oncotic pressure and of fluid distribution between body compartments [ 1 , 2 , 3 , 4 , 5 , 6 ]. Moreover, HSA is the main carrier of endogenous and exogenous ligands, including fatty acids (FAs), nucleic acids, hormones, metals, toxins, and drugs, accounts for most of the pro- and anti-oxidant capacity of plasma, and displays (pseudo-)enzymatic properties [ 4 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Furthermore, HSA plays a pivotal role in heme scavenging acting as a depot and a carrier of the macrocycle; in fact, HSA transfers the macrocycle from high- and low- density lipoproteins (i.e., HDL and LDL, respectively) to hemopexin.…”
Section: Introductionmentioning
confidence: 99%